THE MECHANISM OF LEGAL MARRIAGE PREVENTION AND CANCELLATION BASED ON ISLAMIC LAW COMPILATION - Zakiah Zakiah Zakiah (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
This study aims to find out the legal mechanisms of marriage prevention and cancellation as well as the position of the children in cases of cancelled or prevented marriage. The method used in the writing of this journal is a qualitative method with data collection techniques of literature research which is then analyzed within the technique of descriptive analysis. The results of the study indicate that the legal provisions of the mechanism of prevention and cancellation of marriage can be done by applying for the prevention or the cancellation of a marriage to the Court / Religious Court in which the husband or wife resides or where the marriage takes place. The procedure for filing a marriage cancellation is done in accordance with the procedure for filing a divorce suit. The provisions of article 76 of the compilation of Islamic law has guaranteed a legal protection of the child from a cancelled marriage. The compilation of Islamic law also confirms that the cancellation of a marriage will not break the legal relationship between the child and his or her parents. Based on the results of the research, it is fund out that the government needs to pay attention and improve the weaknesses and the lack of regulation in terms of the prevention and the cancellation of marriages.